Municipal solid waste management in Perlis : status, problems and challenges - Boonsie Cassyrenna A/P Bun Chu (School of Environmental Engineering University Malaysia Perlis, 2011)
Current solid waste management was a major problem in most developing countries. Interview and questionnaires survey on SWM has been done to identfy the current status, problems and challenges in Perlis. From the research survey done, there were lot of problems occur in this state. Among them are unproper solid wastes disposal, rubbish are not regular arranged, lack of waste container, along with inefficient waste collection and transportation processes. Other problem are lack of management and maintenance of compactor lorry and poor public awareness on SWM problem. Besides, there is no recycle method been done for now such as low implementation in 3R programmed. Disposal site around Perlis never been provided with a proper treatment and the method of dispose also uncontrollable. Among them are open burning and illegal dumping which is increased the environmental pollution.